Children's active travel, local activity spaces and wellbeing: A case study in Perth, WA - Babb, C.; Olaru, D.; Curtis, Carey; Robertson, D. (2016)
Children's neighborhood spaces have the potential to enhance their wellbeing by affording active and independent travel. Drawing on a case study of 49 children aged between 9 and 13, living in a suburb of Perth, Western Australia, this study adopts a capability approach to understand how children's travel in the neighborhood environment supports their wellbeing. A mixed methods approach is used to explore children's activity spaces: 1) GPS tracks; 2) children's activity diaries; 3) surveys; and 4) children's photo/pictorial collages. Activity spaces and affordances are used to inform the capability framework. We compare the realized local activity spaces (as confidence ellipses) to the potential activity spaces, indicative of the children's potential to achieve wellbeing, and draw on children's photographic and pictorial evaluations of their neighborhood to provide a qualitative perspective on the range of affordances. The results show substantial constraints to the children's active travel and independent mobility, contrasting with the positive view of the neighborhood the children hold. Children were mainly chauffeured at short distances that could have easily been walked or cycled, yet the photo-collage reveals a rich diversity of places and activities children access and desire to reach and use. The capability framework offers insight into some of the factors limiting children's travel, but also highlights the agency children have in shaping their own travel behavior.